Mathematical Problem Solving and Its Teaching: Study from Indonesian Preservice Teachers - Wed Giyarti; Sumbaji Putranto; Sofyan Tio Fajar Maulana (Universitas Swadaya Gunung Jati, 2025)
This research aims to explore the understanding of preservice mathematics teachers in Indonesia regarding mathematics problems, problem-solving, and learning to develop problem-solving. The research used an exploratory sequential design which consists of two stages, involving quantitative and qualitative. The quantitative stage was carried out through a survey of 124 preservice mathematics teachers. Data was collected using a questionnaire given via Google Forms. Data was analyzed using descriptive statistics and an independent sample t-test. The qualitative stage was carried out through semi-structured interviews with 20 participants. Qualitative analysis adapting the Bogdan and Biklen technique, through data reduction, looking for themes and relationships between themes, and concluding. The results showed that the understanding of preservice mathematics teachers in Indonesia regarding problem solving and learning is in the sufficient category. The results of the independent sample t-test show that students who have studied for more than two years have a better understanding than those who have studied for less than two years. Several lecture activities that influence their understanding are project learning, exercises, and discussions. The result gave considered higher education or universities in providing an accommodating curriculum for students to develop their understanding of problem-solving and its teaching.